Photothermally enhanced antibacterial wound healing using albumin-loaded tanshinone IIA and IR780 nanoparticles - Chen, Haidong; Li, Yimei; Chen, Dexuan; Fang, Yong; Gong, Xuchu; Wang, Kaikai; Ma, Chaoqun (Frontiers in Bioengineering and Biotechnology, 2024)
This study developed a novel nanoparticle formulation to enhance wound healing in bacterial-infected wounds, utilizing albumin as a carrier for the active components Tanshinone IIA and the near-infrared photothermal agent IR780. These nanoparticles were designed to harness both the antimicrobial properties of Tanshinone IIA and the photothermal effects of IR780 under near-infrared laser irradiation. The successful synthesis of these dual-functional nanoparticles was demonstrated through various characterizations, including Transmission Electron Microscopy (TEM) and spectroscopic analysis. The photothermal properties of the nanoparticles significantly enhanced bacterial eradication and facilitated the controlled release of Tanshinone IIA, leading to an accelerated wound healing process. In vitro studies highlighted the superior antibacterial activity of the nanoparticles, especially under photothermal activation, which substantially reduced bacterial viability in cultures of methicillinresistant Staphylococcus aureus (MRSA). Moreover, in vivo experiments using a mouse model of MRSA-infected wounds revealed that the nanoparticle treatment with near-infrared laser irradiation substantially improved wound closure rates compared to controls and treatments without photothermal activation. Statistical analysis was performed using two-way ANOVA followed by Tukey's post-hoc test, ensuring robust evaluation of group differences. By the 16th day post-treatment, significant differences in wound healing rates were evident, demonstrating the effectiveness of the combined photothermal and pharmacological approach. These findings suggest that albuminloaded nanoparticles containing Tanshinone IIA and IR780, activated by near-infrared light, could be a promising therapeutic strategy for treating chronic and infected wounds, offering a multifunctional approach to managing wound infections and inflammation while promoting rapid tissue repair.